Thriving Rough Sets 10th Anniversary - Honoring Professor Zdzisław Pawlak's Life and Legacy & 35 Years of Rough Sets - Wang, Guoyin; Skowron, Andrzej; Yao, Yiyu.; Ślęzak, Dominik; Polkowski, Lech.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This special book is dedicated to the memory of Professor Zdzisław Pawlak, the father of rough set theory, in order to commemorate both the 10th anniversary of his passing and 35 years of rough set theory. The book consists of 20 chapters distributed into four sections, which focus in turn on a historical review of Professor Zdzisław Pawlak and rough set theory; a review of the theory of rough sets; the state of the art of rough set theory; and major developments in rough set based data mining approaches. Apart from Professor Pawlak's contributions to rough set theory, other areas he was interested in are also included. Moreover, recent theoretical studies and advances in applications are also presented. The book will offer a useful guide for researchers in Knowledge Engineering and Data Mining by suggesting new approaches to solving the problems they encounter.
Part 1: Historical Review of Professor Zdzisław Pawłak and Rough Set -- The Born and Growing of Chinese Rough Set Community with Help of Professor Zdzisław Pawłak -- Zdzisław Pawłak as I Saw Him and Remember Him Now -- Recent Development of Rough Computing: A Scientometrics View -- Part 2: Review of Rough Set Research -- Rough Sets, Rough Mereology and Uncertainty -- Rough Sets in Machine Learning: A Review -- Application of Tolerance Rough Sets in Structured and Unstructured Text Categorization: A Survey -- Medical Diagnosis: Rough Set View -- Rough Set Analysis of Imprecise Classes -- Pawłak's Many Valued Information System, Non-deterministic Information System, and a Proposal of New Topics on Information Incompleteness Toward the Actual Application -- Part 3: Rough Set Theory -- From Information Systems to Interactive Information Systems -- Back to the Beginnings: Pawłak's Definitions of the Terms Information System and Rough Set -- Knowledge and Consequence in AC Semantics for General Rough Sets -- Measuring Soft Roughness of Soft Rough Sets Induced by Covering -- Rough search of vague knowledge -- Vagueness and Uncertainty: An F-Rough Set Perspective -- Directions of Use of the Pawłak's Approach to Conflict Analysis -- Lattice Structure of Variable Precision Rough Sets -- Part 4: Rough Set Based Data Mining -- Mining for Actionable Knowledge in Tinnitus Datasets -- Rough-Granular Computing for Relational Data -- The Boosting and Bootstrap Ensembles for the Pair Classifier Based on the Dual Indiscernibility Matrix.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence